Analisis Faktor Kendala Hak Pendirian Rumah Ibadah: Strategi Komunikasi Politik Masyarakat Cilegon Dalam Menolak Hak Pendirian Rumah Ibadah - Mohamad Ikrom Arasid (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This paper examines the case of the rejection of the right to establish a house of worship that triggered action and a petition signed by local officials. There are factors that hinder the right to establish a house of worship and the community's strategy in forming the Cilegon Local Wisdom Rescue Committee. This research study focuses on the city of Cilegon. Qualitative descriptive method used with a case study approach. Factors that hinder the right to establish a house of worship for non-Muslims in the city of Cilegon are historical factors, an agreement prohibiting the establishment of a house of worship except for Islamic, regulations, gratification of non-Muslim groups to some members of the community and the government's lack of responsiveness. The Cilegon Local Wisdom Rescue Committee was formed through a political communication strategy that includes figures and institutional strengthening, togetherness and consensus. The resolution of the conflict can be done through dialogue, mediation, pluralism education, regulations, ethical development, budget availability, involvement of community groups to participate as implementers in the implementation of religious moderation, optimization of the government's role in facilitating community needs with the principles of professionalism, accountability and responsiveness in accordance with the main tasks and functions with applicable procedures.